Supernumerary Marker Chromosome Identified in Asian Elephant (Elephas maximus) - Cernohorska, Halina; Kubickova, Svatava; Musilova, Petra; Vozdova, Miluse; Vodicka, Roman; Rubes, Jiri (Animals, 2023)
We identified a small, supernumerary marker chromosome (sSMC) in two phenotypically normal Asian elephants (Elephas maximus): a female (2n = 57,XX,+mar) and her male offspring (2n = 57,XY,+mar). sSMCs are defined as structurally abnormal chromosomes that cannot be identified by conventional banding analysis since they are usually small and often lack distinct banding patterns. Although current molecular techniques can reveal their origin, the mechanism of their formation is not yet fully understood. We determined the origin of the marker using a suite of conventional and molecular cytogenetic approaches that included (a) G- and C-banding, (b) AgNOR staining, (c) preparation of a DNA clone using laser microdissection of the marker chromosome, (d) FISH with commercially available human painting and telomeric probes, and (e) FISH with centromeric DNA derived from the centromeric regions of a marker-free Asian elephant. Moreover, we present new information on the location and number of NORs in Asian and savanna elephants. We show that the metacentric marker was composed of heterochromatin with NORs at the terminal ends, originating most likely from the heterochromatic region of chromosome 27. In this context, we discuss the possible mechanism of marker formation. We also discuss the similarities between sSMCs and B chromosomes and whether the marker chromosome presented here could evolve into a B chromosome in the future.
Keywords: laser microdissection; sSMC; heterochromatin; FISH; small supernumerary marker chromosome; savanna elephant; Asian elephant; karyotype; NOR